Sistem Pengendalian Persediaan Menggunakan Metode Moving Average dan Pengembangan Sistem Extreme Programming - Alamsyah, Dedy; Damuri , Amat; Nuraini, Rini; Septarini, Ri Sabti; Yudaningsih, Nunik (LPPM POLITEKNIK LP3I BANDUNG, 2022)
Inventory of goods is one of several important factors in a company, whether engaged in trading or manufacturing. It is important for inventory to be controlled and supervised in the recording and calculation of inventory, this is because inventory can affect financial reporting. If the amount of inventory is too large (overstock), on the other hand, if the inventory is a little, it will have an impact on the lack of inventory (stockout). The purpose of this research is to develop an inventory control system using the moving average method and the development of an Extreme Programming (XP) system. The moving average method in inventory prediction is more effective because this method compares current and previous data. To develop the system, the Extreme Programming (XP) system development method is used. This method has advantages including: fast process, time and cost efficiency, low risk, flexibility and easy to implement. From the test results using black box testing by testing the functionality, the system shows the system has met expectations with a value reaching 100%. Meanwhile, for testing with the DeLone and McLean models which measure the success of information systems, the score reaches 81.37%.